Implementasi Kebijakan Dana Desa Dalam Mengentaskan Kemiskinan: Studi Kasus Di Desa Dendun Kecamatan Mantang - Melia Indriyani; Merinasilvi Merinasilvi; Vini Suri Liandrainy (CiDEA Journal, 2024)
The poverty level in remote villages, especially Dendun Village, which is located on the coast of Bintan, is still quite high, because most coastal communities work as fishermen and have unstable incomes. The concrete effort made by the government is to implement the Village Fund Policy in the APBN. Village Fund allocations have been implemented since the 2015 APBN and are part of the Transfer Fund allocation. In 2023, the Village Fund (DD) allocation in Dendun Village will be IDR. 853,646,000.00. These Village Funds are used to finance the implementation of village government, implementation of village development, development of village communities, and empowerment of village communities. This research is qualitative in nature using secondary data obtained from the Dendun Village Head and Village Secretary, where there are five programs implemented in 2023 sourced from the Village Fund. The purpose of this writing is to find out what programs will be implemented from the Village Fund in 2023 and what impact they will have in alleviating poverty for the community in Dendun Village.